Electronic Literature Experimentalism beyond the Great Divide: A Latin American Perspective - Kozak, Claudia (2020)
It may be true that contemporary digital culture is by now deeply rooted in everyday life of an important part of world's population–including our habits of writing and reading. Yet digital literature remains more or less invisible to most people. Many people can feel "at home" within digital everyday life and, still, consider that literature is only something related to print books, at most digitized. Regarding this–at first sight– paradoxical situation, I will argue that its cause lies in the strong experimental impetus that digital literature has entailed since its first appearances in mid- 20th century. E-lit has kept this impetus up to the present; therefore, it stays under larger audiences' radar; audiences who in general play along with mainstream digital culture. However, from my standpoint this e-lit experimentalism, which does not easily accept the whole predigested package of digital culture in its mainstream form and meaning, may also open interesting possibilities to building disruptive perceptual and cognitive experiences at a larger scale contesting hegemonic digital culture. One condition to accomplish such an endeavor, though, would be to surpass the reproduction of the–in part rejected since the sixties–"Great Divide" (Huyssen) between high and lowbrow culture or, maybe in a more accurate description of nowadays culture, between smaller but highly selfreflective audiences and broader, usually less reflective ones...